Analysing the impact of agile supply chain on firms' sales performance with moderating effect of technological-integration. (7th May 2019) - Alam, M.D. Sarwar-A; Wang, Daoping; Waheed, Abdul; Khan, Muhammad Shahid; Farrukh, Muhammad
Agility has become a key driver for all business operations, including supply chain (SC) operations to convene the requirements of the customers in a timely manner. The concept of agility with respect to SC is accelerating therefore sparse literature accessible on such domain, especially with incorporation of technology (TE) from developing economies. The current study investigates the linkages between distinct dimensions of the agile supply chain (ASC) and firms' sales performance (FSP) by adopting moderating effect of TE within SMEs of Bangladesh. Data collected from SC managers and evaluated using structural equation modelling. The findings affirmed the positive relationships between ASC and FSP along with positive connection of each dimension of ASC, i.e., alertness (ART), flexibility (FXB), decisiveness (DSV), swiftness (SWT), and accessibility (ACB). A positive influence of TE is found between ASC and FSP, respectively. This study presents insights for strategic SC management to focus ASC and TEs' capabilities in order to optimise FSP in today's customer-oriented era.